Chronic pain persists in adults with sickle cell disease despite regular red cell transfusions. (August 2019) - Karafin, Matthew S.; Mullins, Danielle E.; Johnson, Susan T.; Nischik, Debora; Feng, Mingen; Simpson, Pippa; Field, Joshua J.
Abstract: Background: Pain affects over 50% of adults with sickle cell disease (SCD), and this pain is largely managed outside of the hospital. While chronic transfusion therapy is used to decrease the rate of acute pain events in patients with SCD, less is known about its impact on the day-to-day experience of pain. To address this knowledge gap, we provided pain diaries to patients with SCD receiving chronic transfusion. Patients and Methods: A convenience sample of chronically-transfused adults with SCD successfully completed a diary over the course of at least 2 transfusion events. Patients receiving simple transfusions and red cell exchanges were included. Pain was rated on a scale of 0 to 10 each day, and patient laboratory values, co-morbidities, and hospital utilization were also obtained using the electronic medical record. The mean pain scores pre- and post-transfusion were evaluated using both a random effects-expectation maximization regression tree analysis and a generalized linear mixed regression model. Results: Ten subjects (63%) in this cohort were defined as having chronic pain, while the remaining four (27%) subjects had episodic pain. Despite chronic transfusion and a suppressed HbS% (22.5% (16.5-25.9)), 10 patients (63%) continued to report nearly daily pain, and on almost 70% of diary days, the pain was significant (≥5/10). When the relationship between HbS% and reported pain intensity was examined, no association was found. Discussion: These results suggest that, even with regular transfusions and a low HbS%, daily pain persists in many adults with SCD.